Forschungen zu den Lokalmythen griechischer Städte. Die sogenannten Patriatraditionen - Nollé, Johannes (e-Forschungsberichte des DAI, 2017)
Many classicists, especially classical philologists and archaeologists, still regard panhellenic myths as the real embodiment of Greek Mythology, even if they acknowledge the existence of some local deviations. In fact, in contrast to this widely shared supposition, each Greek polis had its own mythical traditions, which were called ‘ta pátria’ and these form the nucleus of Greek Mythology. Panhellenic myths are for the most part delocalized mythical tales. Local lore played a major role in creating an ancient city’s identity and is therefore of the utmost importance for all branches of Classical Studies. Over the last years J. Nollé has concentrated on bringing together the scattered evidence of single cities’ mythical traditions, in particular by basing his research work on numismatic evidence. This research has shed new light on the way in which many Greek cities conceived and understood their own identity as well as on the general function of mythical traditions in Greek society.